Cretaceous eustasy revisited - Haq, Bilal U. (Global and planetary change, 2014)
Eustatic sea-level changes of the Cretaceous are reevaluated based on a synthesis of global stratigraphic data. A new terminology for local/regional or relative sea-level changes (eurybatic shifts) is proposed to distinguish them from global (eustatic) sea-level changes, with the observation that all measures of sea-level change in any given location are eurybatic, even when they include a strong global signal. Solid-earth factors that influence inherited regional topography and thus modify physical measures of amplitude of the sea-level rises and falls locally are reviewed. One of these factors, dynamic topography (surface expression of mass flow in the upper mantle on land- and seascapes), is considered most pertinent in altering local measures of amplitude of sea-level events on third-order time scales (0.5–3.0Myr). Insights gained from these models have led to the reconciliation of variance between amplitude estimates of eurybatic shifts in any given region and global measures of eustatic changes. Global estimates of third-order events can only be guesstimated at best by averaging the eurybatic data from widely distributed time-synchronous events. Revised curves for both long-term and short-term sea-level variations are presented for the Cretaceous Period. The curve representing the long-term envelope shows that average sea levels throughout the Cretaceous remained higher than the present day mean sea level (75–250m above PDMSL). Sea level reached a trough in mid Valanginian (~75m above PDMSL), followed by two high points, the first in early Barremian (~160–170m above PDMSL) and the second, the highest peak of the Cretaceous, in earliest Turonian (~240–250m above PDMSL). The curve also displays two ~20Myr-long periods of relatively high and stable sea levels (Aptian through early Albian and Coniacian through Campanian). The short-term curve identifies 58 third-order eustatic events in the Cretaceous, most have been documented in several basins, while a smaller number are included provisionally as eustatic, awaiting confirmation. The amplitude of sea-level falls varies from a minimum of ~20m to a maximum of just over 100m and the duration varies between 0.5 and 3Myr. The causes for these relatively rapid, and at times large amplitude, sea-level falls in the Cretaceous remain unresolved, although based mainly on oxygen-isotopic data, the presence of transient ice cover on Antarctica as the driver remains in vogue as an explanation. This idea has, however, suffered a recent setback following the discovery of pristine foraminiferal tests in the Turonian of Tanzania whose oxygen-isotopic values show little variation, implying absence of glacioeustasy at least in the Turonian. The prevalence of 4th-order (~400Kyr) cyclicity through most of the Cretaceous (and elsewhere in the Paleozoic, Jurassic and Cenozoic) implies that the periodicity on this time scale, presumably driven by long-term orbital eccentricity, may be a fundamental feature of depositional sequences throughout the Phanerozoic.